Identification of the BRAF V600E mutation in a patient with sclerosing pneumocytoma: A case report. (November 2019) - Jiang, Guanming; Zhang, Min; Tan, Qinquan; Lin, Shunhuan; Zeng, Yihong; Liu, Chun; Chen, Rongrong; Zhou, Jianping
Highlights: BRAF V600E is common in malignant tumor, like melanoma and NSCLC. Sclerosing pneumocytoma is a rare benign tumor. Sclerosing pneumocytoma has limit data in genomic research. It's the first report that BRAF V600E was found in a young sclerosing pneumocytoma. The report extended understandings of pathogenesis of sclerosing pneumocytoma. Abstract: Objectives: Sclerosing pneumocytoma (sclerosing hemangioma, SP) is a rare benign tumor of the lung with a low risk of recurrence. The genomic profile of SP is not well-known. Here we report gene mutation findings in a 17-year-old girl with SP. Materials and methods: Immunohistochemistry (IHC), next-generation sequencing (NGS), and sanger sequencing were performed on the tumor tissue of this patient for pathological diagnosis and gene mutation analysis. Results and conclusion: Two mutations were identified in the tumor tissue by NGS and sanger sequencing: AKT1 E17K and BRAF (B-Raf proto-oncogene, serine/threonine kinase) V600E. This is the first case report of a BRAF V600E mutation in a patient with SP. This discovery extends our understanding of the pathogenesis of SP, and suggests the need for future testing of BRAF V600E in this rare tumor type.